2021
DOI: 10.1159/000517574
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Back Pain among German Ophthalmologists

Abstract: <b><i>Introduction:</i></b> The aim of this study was to evaluate the prevalence of back pain among German ophthalmologists, to investigate the relationship towards age, gender, various profession-related factors, to correlate localization of pain to subspecialties, and to explore individual therapeutic and coping strategies. <b><i>Methods:</i></b> In this prospective, cross-sectional survey, a 9-item questionnaire was sent via mail to all members of the German p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…Auch bei deutschen präklinischen Rettungskräften waren Schmerzen in Nacken und Rücken die häufigsten Beschwerden in den letzten 12 Monaten (Möckel et al 2022). Im Vergleich dazu zeigte eine Studie mit 1807 Augenärztinnen und -ärzten, dass zum Zeitpunkt der Erhebung 81 % der Teilnehmenden unter Rückenproblemen litten (Bertelmann et al 2021), was einem höheren Anteil als in der vorliegenden Studie entspricht. In der Allgemeinbevölkerung liegt die bekannte 12-Monats-Prävalenz von Rückenschmerzen bei etwa 61 % sowie Nackenschmerzen bei 48 % (von der Lippe et al 2021).…”
Section: Variablenunclassified
See 1 more Smart Citation
“…Auch bei deutschen präklinischen Rettungskräften waren Schmerzen in Nacken und Rücken die häufigsten Beschwerden in den letzten 12 Monaten (Möckel et al 2022). Im Vergleich dazu zeigte eine Studie mit 1807 Augenärztinnen und -ärzten, dass zum Zeitpunkt der Erhebung 81 % der Teilnehmenden unter Rückenproblemen litten (Bertelmann et al 2021), was einem höheren Anteil als in der vorliegenden Studie entspricht. In der Allgemeinbevölkerung liegt die bekannte 12-Monats-Prävalenz von Rückenschmerzen bei etwa 61 % sowie Nackenschmerzen bei 48 % (von der Lippe et al 2021).…”
Section: Variablenunclassified
“…Es ist bekannt, dass Personen in Gesundheitsfachberufen häufig unter Schmerzen leiden (Bertelmann et al 2021;Hönl et al 2021;Möckel et al 2021Möckel et al , 2022Steiner u. Möckel 2021). In einer Studie mit Augenärztinnen und Augenärzten aus Deutschland berichteten etwa vier von fünf Teilnehmenden über Rückenbeschwerden, wobei das weibliche Geschlecht, höheres Alter und mehr Jahre Berufserfahrung in den Untersuchungen als Risikofaktor angegeben wurden (Bertelmann et al 2021). Eine Analyse von Ärztinnen und Ärzten aus dem Kanton Zürich, Schweiz, zeigte, dass 36,6 % unter einem chronischen Gesundheitsproblem und 64,6 % an geringfügigen muskuloskelettalen Beschwerden litten.…”
Section: Introductionunclassified
“…In the period preceding the COVID-19 pandemic, as many as 40-80% of employees who used a computer continuously in the course of their duties had musculoskeletal dysfunctions [3][4][5][6]. During the pandemic, among healthcare professionals using computers at work, the most common pathology of the musculoskeletal system was pain in the cervical spine and/or shoulder associated with incorrect ergonomics of the workplace and working time (long working hours, prolonged use of the computer, sedentary work, lack of changes in posture during work) [7,8]. At the same time, the duration of pain depended to a large extent on the age of employees and seniority [9].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 154 studies revealed an estimated lifetime prevalence of LBP in healthcare personnel of 54.8% [ 6 ]. LBP prevalence has been found to be higher among dentists and nurses than among other health professionals, and ophthalmologists specializing in surgery have been shown to experience LBP more frequently (53%) than professionals who perform other medical duties [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 154 studies revealed an estimated lifetime prevalence of LBP in healthcare personnel of 54.8% [6]. LBP prevalence has been found to be higher among dentists and nurses than among other health professionals, and ophthalmologists specializing in surgery have been shown to experience LBP more frequently (53%) than professionals who perform other medical duties [7,8]. In addition to doctors and healthcare professionals, medical students experience high rates of LBP, with causes that include smoking, stress, poor sleeping posture, and family history [9].…”
Section: Introductionmentioning
confidence: 99%